1969
DOI: 10.1002/ar.1091640204
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of growth hormone‐ and prolactin‐containing acidophils with peroxidase‐labeled antibody

Abstract: In order to verify the concept that growth hormone and prolactin are contained in two different populations of acidophils, sections of Bouin-fixed rat hypophyses were stained immunochemically. For this purpose the histochemical demonstration of peroxidase was utilized after sequential application to the tissue section of rabbit antiserum to human growth hormone (or antiserum to rat prolactin) followed by application of peroxidase-labeled sheep antiserum to rabbit gamma-globulin. It was found that growth hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

1970
1970
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 14 publications
5
14
0
Order By: Relevance
“…Furthermore, studies by Costoff and McShann [5], based on isopycnic gradient centrifugation, demonstrated that 95% of GH biologi cal activity was found in a zone containing secretory granules havlr>g a maximum diameter of 350 nm. These data are supported by immunofluorescence studies of Shiino and Rennets [30] and immunoperoxidase-labeled antibody data [3,17].…”
Section: Identification O F Somatotrophssupporting
confidence: 68%
“…Furthermore, studies by Costoff and McShann [5], based on isopycnic gradient centrifugation, demonstrated that 95% of GH biologi cal activity was found in a zone containing secretory granules havlr>g a maximum diameter of 350 nm. These data are supported by immunofluorescence studies of Shiino and Rennets [30] and immunoperoxidase-labeled antibody data [3,17].…”
Section: Identification O F Somatotrophssupporting
confidence: 68%
“…2-4) highlight the im pact of the ovary on these two cell types. In the case of mammotrophs, these modifications can be explained by a direct action of estrogens on the AP [16,22,30], Immuno stained mammotrophs were judged larger and more numer ous in adult female rats than in either adult males or ova riectomized females [4]. Estrogens may also have an indirect effect via the hypothalamus: an acute effect of estradiol is to suppress secretion of dopamine into the hypophyseal portal blood [10], which probably results in enhanced mammo troph secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Only the com parison w ith the lightm icroscopy image obtained from a th ick section of th e sam e tissue block allows some degree of c e rtain ty . Of all the m ethods of approach which have been followed in the stu d y of the functional significance of the different hypophyseal cell tvpes, the technique of im m unochem istry appears to be the m ost specific and to hold the greatest prom ise for future progress [Baker, 1969].…”
Section: Discussionmentioning
confidence: 99%